Electric Field - Sheikholeslami Kandelousi, Mohsen (IntechOpen, 2018)
In the present book, various applications of electric field are introduced in health and biology like treating cancer and cell sorting and in engineering and technological applications like enhancing the heat transfer, colloidal hydrodynamics and stability, and lithography. Electric field is defined as a force field arising from the electric charges. Depending on the nature of the material (the ability to polarize) and the inherent or attained surface charges, the response of the electric field varies.